Short communication: Diversity and ethnobotany of Araceae in Namo Suro Baru Village, North Sumatra, Indonesia - RIDAHATI RAMBEY; EDO RAYVALDO PURBA; ADRIAN HARTANTO; BAGUS PRIO PRAKOSO; PENIWIDIYANTI PENIWIDIYANTI; LASWI IRMAYANTI; MAHARDIKA PUTRA PURBA (Society for Indonesian Biodiversity, 2022)
Abstract. Rambey R, Purba ER, Hartanto A, Prakoso BP, Peniwidiyanti, Irmayanti L, Purba MP. 2022. Short communication: Diversity and ethnobotany of Araceae in Namo Suro Baru Village, North Sumatra, Indonesia. Biodiversitas 23: 6006-6012. For Indonesian people, the variety of Araceae species has risen to prominence as an ornamental plant and a supplemental food source. However, there is still a lack of information about some species and their cultivation in some parts of North Sumatra. This research was conducted in the village of Namo Suro Baru, Biru-Biru District, Deli Serdang, North Sumatra to identify and study the ethnobotanical use of the species of Araceae. A total of 48 plots, each measuring 2 × 2 m were constructed, and 30 respondents from the community were interviewed about the local utilization of aroids. The results of vegetation analysis recorded a total of 17 species of Araceae plants in the village of Namo Suro Baru in Biru-Biru District, Deli Serdang Regency, North Sumatra Province. Xanthosoma sagittifolium was the dominant species with the highest IVI, i.e. 40.44%, while Dieffenbachia seguine had the lowest IVI (0.86%). The parts of the plant that the locals had traditionally used were the tuber, petiole, and whole leaf. The four main purposes of using Araceae plants were classified as foods, feeds, herbal formulations or medicines, and ornamental plants. Two species of corpse flowers, Amorphophallus titanum and A. prainii, also periodically bloomed in the village, but because they are protected species, the locals did not use them for their needs.